Business models for freight and logistics services - Niclas Meyer; Djerdj Horvat; Matthias Hitzler; Claus Doll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
This paper discusses a range of business model innovations taking place out-side the rail transport sector with a direct impact on rail transport. The paper also discusses business model innovations that may have been developed elsewhere but could be transferred to the rail transport sector. The paper's main research question is whether business model innovations have the potential to strengthen the rail transport sector. While the focus is on how to increase the market share of rail transport in the modal split, it is not exclusively on business model innovations within the rail transport sector. It will also look at business model innovations outside the rail transport sector with the potential to increase the modal market share of rail transport. This paper is based on a survey of all business model innovations within the rail transport sector and relevant innovations outside the sector.
urn:nbn:de:0011-n-4943516; Additional information: Working Paper 4 of the study LowCarb-RFC - European Rail Freight Corridors going Carbon Neutral.
Keywords: 330